Ultrafiltration trough peritoneal dialysis in refractory congestive heart failure patients: one center experience - Mehmet Fethullah Aydın; Ayşegül Oruç; Alparslan Ersoy; Abdulmecit Yildiz; Mahmut Yavuz; Kamil Dilek; Mustafa Güllülü (Turkish Journal of Internal Medicine, 2020)
Background: Hypervolemia is an important consequence of heart failure (HF) that leads to poor quality of life and frequent hospitalizations. Ultrafiltration (UF) with dialysis is an option for HF patients who are resistant or inappropriate for diuretics. Peritoneal dialysis (PD) can be a long-term efficient solution for hypervolemia in appropriate HF patients. Material and Methods: We retrospectively evaluated PD patients in our center in order to determine the ones whose indication was UF for volume control because of HF between January 2015 and January 2020. Results: 4 (2 females, 68.75±4.27 years old) HF patients who had a poor volume control on diuretic based regimen were on PD for UF. PD treatment was planned as a daily single exchange with icodextrin in whom all had preserved renal function. In one patient one daily exchange with an amino acid-based PD solution was added. The exchange volume was between 1000 and 1500 mL, dwell time was 9 to 14 hours, and UF was 200 to 1100 mL. During the follow-up, patients lost adequate weight and none of them were hospitalized because of hypervolemia. Conclusions: UF through PD in HF patients provides effective volume control, relief of symptoms, and avoids frequent hospitalizations. A single daily exchange with icodextrin can be adequate for hypervolemic, well-selected HF patients.